Effects of thermal pretreatment and ex-situ grinding on the pyrolysis of mallee wood cylinders - Jiang, S.; Hu, X.; Shao, X.; Song, Y.; Xia, D.; Li, Chun-Zhu (Elsevier, 2017)
© 2017 Elsevier B.V.This study investigated the effects of thermal pretreatment and ex-situ grinding on the production of bio-oil and biochar from the pyrolysis of mallee wood cylinders in a fluidised-bed reactor. The wood cylinders were firstly pretreated at 150–380 °C and were then crushed into small particles before further pyrolysis at 500 °C. Thermal pretreatment alone for wood cylinders could not promote the bio-oil yield. Combined thermal pretreatment at low temperatures and subsequent grinding facilitated the formation of bio-oil and minimised the formation of biochar. This is because the thermal pretreatment and grinding partially destroyed the cell wall structure and improved the mass transfer of volatiles exiting from the particles during the subsequent pyrolysis. However, if the pretreatment temperature was above 260 °C, the biochar yields increased due to the cross-linking and charring reactions. These charring reactions compromised the beneficial effects of grinding, leading to decreases in the formation of bio-oil. The balance between thermal pretreatment and grinding needed to be delicately managed to maximise the formation of bio-oil. The pretreatment temperature would significantly affect the composition of bio-oil from the ex-situ grinding pyrolysis. The controlled pretreatment temperature could somewhat “activate” lignin or cause cross-linked bonds in biomass which was responsible for the formation of aromatics.